Produção de forrageiras hibernais semeadas antes e após a colheita da soja, sob doses de adubação nitrogenada - Ortiz, Sidney (2014)
The study was conducted in the experimental area of the Federal Technological University of Paraná (UTFPR), Campus Pato Branco, with the objective of evaluating the effect of the establishment of cool season forages before and after harvest of soybean (Glycine max Merrill) and nitrogen use production and nutritional value of forage. The seeding of forage species was broadcasted before soybean harvest, when that found in the reproductive phenological stage R5, and after harvest, sowing in rows. The experimental design was completely randomized, split-plot, distributed in a 3x3 factorial arrangement , three cool season forages three nitrogen with three replications. In the main plots were allocated sowing times, subplots and subsubplots, the combination of nitrogen and forage species. The forages used were oat (Avena strigosa Schreb.) Cv. IAPAR 61, common ryegrass (Lolium multiflorum Lam) and common vetch (Vicia sativa L.) to sowing density of 80, 40 and 35 kg ha-1 of viable seeds, respectively. The levels of nitrogen as urea, were 0, 150 and 300 kg ha-1, applied in bands divided into two applications. The sowing of fodder before the soybean harvest is possible to anticipate the first grazing, obtaining higher production of dry matter per hectare (ryegrass and oats) with better quality, greater efficiency and N recovery and reduce the deficit forage in the fall. Nitrogen does not influence forage yield of vetch and fiber content of the forage. Level of 150 and 300 kg ha-1 N in yield and quality of forage similar, but the level of 150 kg N ha-1 shows greater recovery and utilization efficiency.